A method for preparing titanium dioxide nanotube arrays on the surface of Ti-13Nb-13Zr alloy

Through a specific electrolyte formulation and anodization method with controlled parameters, the problem of uneven preparation of titanium dioxide nanotube arrays on the surface of Ti-13Nb-13Zr alloy was solved, and low-cost, high-performance nanotube array preparation was achieved, which is suitable for biomedical applications.

CN115787027BActive Publication Date: 2025-10-03CHANGZHOU UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211708072.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2025-10-03
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

Existing technology makes it difficult to effectively prepare titanium dioxide nanotube arrays on the surface of Ti-13Nb-13Zr alloy under low-cost conditions, and the morphology of the nanotube arrays is not regular enough, which affects their application in the biomedical field.

Method used

Titanium dioxide nanotube arrays were prepared on the surface of Ti-13Nb-13Zr alloy by using a specific electrolyte formula and anodizing parameters, including a mixed solution of ethylene glycol, ammonium fluoride, sulfuric acid and chromium trioxide, combined with a constant temperature water bath and mechanical stirring, and controlling the anodizing voltage and time.

Benefits of technology

It has been achieved that titanium dioxide nanotube arrays with uniform pore size and regular arrangement can be prepared at low voltage, which improves the bonding strength with subsequent coatings, reduces production costs, and is suitable for the biomedical field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004022996610000011
    Figure HDA0004022996610000011
  • Figure HDA0004022996610000012
    Figure HDA0004022996610000012
Patent Text Reader

Abstract

The present invention belongs to the field of titanium alloy surface treatment technology, and specifically relates to a method for preparing a titanium dioxide nanotube array on the surface by anodizing a Ti-13Nb-13Zr alloy at a relatively low voltage. The method uses ethylene glycol, fluoride, sulfuric acid, and chromium oxide as electrolytes to prepare a regularly arranged, high-density titanium dioxide nanotube array. The obtained surface-modified titanium alloy not only has excellent biocompatibility, antibacterial properties, and corrosion resistance, but also has a porous surface structure that greatly improves the adhesion of the coating to the substrate. Therefore, this method provides a new approach for preparing titanium dioxide nanotube arrays by anodizing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of titanium alloy surface treatment, and particularly relates to a method for preparing a titanium dioxide nanotube array on the surface of a Ti-13Nb-13Zr alloy by anodic oxidation at a low voltage. Background Art

[0002] Titanium and its alloys are widely used in medical fields such as dentistry, human implants, orthopedics, and medical devices due to their high specific strength, low elastic modulus, excellent corrosion resistance, and good biocompatibility. The elastic modulus of pure titanium is approximately 80 GPa, which is closest to that of human bone tissue. This facilitates the chemical osseous bonding of implant materials with bone tissue and reduces the mechanical disharmony between the implant material and bone. Therefore, it is often used to repair human hard tissue. Titanium alloys were first used as oral restorative materials and are now widely used as human implant materials. The excellent biocompatibility, bioaffinity, and inertness of titanium alloys have led to their continued expansion in medical applications, and they have now attracted widespread attention.

[0003] The third generation of biomedical β-titanium alloys, represented by Ti13Nb13Zr, uses elements such as Nb, Ta, Zr, Mo, and Sn in place of Al. β-type titanium alloys also offer outstanding properties such as low elastic modulus, good biocompatibility, high specific strength, and excellent corrosion and wear resistance, making their replacement by second-generation alloys an inevitable trend.

[0004] Since Grimes et al. successfully prepared titanium dioxide nanotube arrays on titanium substrates using anodization, scholars at home and abroad have done a lot of research on preparing titanium dioxide nanotube array structures on titanium surfaces using anodization methods.

[0005] The formation of titanium dioxide nanotube arrays is affected by many factors. Studies have shown that changing experimental parameters such as anodic oxidation voltage, electrolyte system, electrolyte acidity, oxidation time, and electrolytic cell temperature all have a certain impact on the morphology and size of titanium dioxide nanotube arrays.

[0006] Patent CN101016637A uses dimethylformamide and 0.1-5% hydrofluoric acid as the main raw materials to prepare an organic electrolyte, and grows a TiO2 nanotube array on a titanium foil through an anodic oxidation reaction. The voltage is 10-40 volts and the anodic oxidation reaction time is greater than 5 hours. The TiO2 nanotube array is more than 20 microns in length, more than 100 nanometers in diameter, and the aspect ratio can reach more than 200.

[0007] Patent CN110923780A prepares an electrolyte with 0.25-0.75wt.% ammonium fluoride, 1-10wt.% water and 89.5-98.5wt.% alcohol solvent, and prepares TiO2 nanotube arrays on the surface of a titanium-containing material by anodic oxidation at a voltage of 15-50V for 30-120 minutes. The thickness of the obtained titanium dioxide nanotube array layer does not exceed 500nm.

[0008] The anodic oxidation voltage depends on the electrolyte system and substrate thickness. The oxidation voltage not only directly affects the formation of the nanotube array but also its microscopic morphology. Studies have shown that if the voltage is too low, the nanotube array structure fails to form, resulting in a sponge-like porous structure. If the voltage is too high, the previously formed nanotube array gradually degenerates into a random porous structure until it disappears completely.

[0009] The higher the HF content in the fluorine-containing electrolyte system, the lower the voltage required to form the nanotube arrays. Within the appropriate oxidation voltage range, the diameter of the titanium dioxide nanotube arrays increases with increasing voltage. Anodic oxidation voltage is the most important factor affecting nanotube diameter. Controlling the oxidation voltage is one of the key techniques for obtaining titanium dioxide nanotube arrays of varying diameters. This requires selecting a specific oxidation voltage for different electrolyte systems and substrate thicknesses to produce nanotube arrays of the desired diameter. Summary of the Invention

[0010] The object of the present invention is to provide a low-cost and continuous production method for preparing titanium dioxide nanotube arrays on the surface of a Ti-13Nb-13Zr alloy.

[0011] The technical solution of the present invention is:

[0012] Nanotube arrays were prepared on the surface of Ti-13Nb-13Zr alloy by anodic oxidation as follows:

[0013] (1) Wire cutting: Wire cutting is performed on Ti-13Nb-13Zr alloy bars to obtain the required samples and then clean them;

[0014] (2) Sample polishing: Use sandpaper to polish the sample, and then polish it with a polishing cloth until the surface is scratch-free and mirror-like;

[0015] (3) preparing an electrolyte: the electrolyte includes ethylene glycol, ammonium fluoride (NH4F), sulfuric acid (H2SO4), chromium trioxide (Cr2O3), and deionized water. The prepared electrolyte is placed in a constant temperature water bath and mechanical stirring is adjusted to ensure uniform mixing.

[0016] (4) Anodization: The sample treated in step (2) is placed in the electrolyte of step (3), and the Ti-13Nb-13Zr alloy sample is used as the anode and the graphite rod is used as the cathode. The anodization voltage and the anodization time are controlled to perform anodization to obtain a titanium dioxide nanotube array on the surface of the Ti-13Nb-13Zr alloy.

[0017] The volume fraction ratio of ethylene glycol to deionized water in the electrolyte used in the present invention is 1:4, the mass fraction of NH4F is 0.3-1wt.%, the mass fraction of H2SO4 is 0.25-0.5wt.%, and the mass fraction of Cr2O3 is 0.3wt.%.

[0018] Preferably, the volume fraction ratio of ethylene glycol and deionized water in the electrolyte is 1:4, the mass fraction of NH4F is 0.5wt.%, the mass fraction of H2SO4 is 0.25wt.%, and the mass fraction of Cr2O3 is 0.3wt.%.

[0019] The anodic oxidation voltage of the present invention is 15-40V, and the anodic oxidation time is 10-60min, preferably the anodic oxidation voltage is 25V, and the anodic oxidation time is 40min.

[0020] Furthermore, a constant temperature water bath is used during the anodization process of the present invention, and the water bath temperature is maintained at 35° C.; and mechanical stirring is used to ensure uniform distribution of the electrolyte during the anodization process, and the mechanical stirring speed is 160 to 180 r / min.

[0021] In the electrolyte preparation process of step (3) of the present invention, the constant temperature water bath temperature is 35° C. and the mechanical stirring speed is 240 r / min.

[0022] The disc cut in step (1) of the present invention has a thickness of 1 mm and a diameter of 10 mm, and is ultrasonically cleaned using deionized water, acetone, and 95% alcohol in sequence.

[0023] In step (2) of the present invention, the sample is polished using sandpaper of #240, #600, #1200, and #2000 in sequence. When the directions of the surface scratches are consistent, the polishing direction is changed orthogonally until the surface is smooth.

[0024] Furthermore, the preparation method of the present invention further comprises sample post-processing: using 95% alcohol to clean the sample obtained by anodization in step (4), and drying it in the air or in an oven.

[0025] The present invention uses a novel electrolyte formula, employing ammonium fluoride and sulfuric acid instead of the traditional hydrogen fluoride electrolyte. This provides more hydrogen ions, which is more conducive to the nanotube formation reaction. The addition of ethylene glycol makes the generated nanotubes smoother, and chromium trioxide promotes the formation of the nanotube structure. This allows for rapid anodization of the Ti-13Nb-13Zr alloy at a relatively low voltage, resulting in a titanium dioxide nanotube array structure while reducing production costs. The Ti-13Nb-13Zr alloy prepared using this method exhibits a complete and neat nanotube array morphology. The Ti-13Nb-13Zr alloy prepared by this method has applications in the biomedical field.

[0026] The main advantages of the present invention are:

[0027] (1) The present invention provides a method for preparing a uniform and regular array of titanium dioxide nanotubes on the surface of a Ti-13Nb-13Zr alloy. The prepared Ti-13Nb-13Zr alloy surface nanostructure has excellent performance. The nanotubes on the Ti-13Nb-13Zr alloy surface have a pore size of up to 15 nm and a porosity greater than 65%. This material has significant improvements in adhesion to subsequent coatings for biomedical applications, better meeting the needs of clinical implantation.

[0028] (2) The present invention provides a new electrolyte formula, and the corresponding anodizing voltage and anodizing time parameters, which can better achieve lower cost production and excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the SEM image of the porous surface morphology obtained in Example 1 of the present invention.

[0030] Figure 2 This is the SEM image of the porous surface morphology obtained in Example 4 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below with reference to the following embodiments: These embodiments are only used to illustrate the present invention and are not used to limit the scope of the invention.

[0032] Example

[0033] The implementation method of the present invention for preparing nanotube arrays on the surface of Ti-13Nb-13Zr alloy is as follows:

[0034] (1) Wire cutting: Ti-13Nb-13Zr alloy rods were wire cut to obtain discs with a thickness of 1 mm and a diameter of 10 mm. The desired samples were then ultrasonically cleaned using deionized water, acetone, and 95% alcohol.

[0035] (2) Sample polishing: Use #240, #600, #1200, and #2000 sandpaper to polish the disc in sequence. When the direction of the surface scratches is consistent, change the polishing direction orthogonally until the surface is relatively smooth. Then use a polishing cloth to polish until the surface is scratch-free and presents a mirror finish.

[0036] (3) preparing an electrolyte: the electrolyte includes ethylene glycol, ammonium fluoride (NH4F), sulfuric acid (H2SO4), chromium trioxide (Cr2O3), and deionized water. The prepared electrolyte is placed in a constant temperature water bath, and the constant temperature water bath temperature is maintained at 35°C. The mechanical stirring speed is adjusted to 240 r / min, and the electrolyte is stirred for 15 minutes to mix uniformly.

[0037] (4) Anodic oxidation: A Ti-13Nb-13Zr alloy sample was used as the anode and a graphite rod as the cathode. The samples were placed in an electrolyte solution while maintaining a constant temperature of 35°C in a water bath and a mechanical stirring speed of 160 r / min. The anodic oxidation voltage and anodic oxidation time were controlled to perform anodic oxidation to obtain a titanium dioxide nanotube array on the surface of the Ti-13Nb-13Zr alloy.

[0038] (5) Sample post-processing: Use 95% alcohol to clean the sample obtained by anodization, dry it naturally or bake it for measurement.

[0039] The following examples and comparative examples differ in electrolyte composition, anodic oxidation voltage and time parameters.

[0040] Example 1

[0041] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 0.5 wt.% NH₄F₂, 0.25 wt.% H₂SO₄, and 0.3 wt.% Cr₂O₃. The anodization voltage was 15 V, and the anodization time was 60 min. After anodization, the alloy was removed and cleaned. Testing revealed that the surface nanotubes of the prepared Ti-13Nb-13Zr alloy initially appeared, but some pores were partially sealed.

[0042] Example 2

[0043] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 1 wt.% NH₄F₂ and 0.5 wt.% H₂SO₄, respectively, and 0.3 wt.% Cr₂O₃. The anodic oxidation voltage was 40 V, and the anodic oxidation time was 10 minutes. Testing revealed that the prepared Ti-13Nb-13Zr alloy surface nanotubes formed a nanotube morphology, but some areas showed sealed pores, while others showed pore wall ablation, leading to pore fusion.

[0044] Example 3

[0045] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 0.5 wt.% NH₄F₂, 0.25 wt.% H₂SO₄, and 0.3 wt.% Cr₂O₃. The anodic oxidation voltage was 30 V, and the anodic oxidation time was 40 minutes. Testing revealed that the nanotubes formed on the surface of the Ti-13Nb-13Zr alloy exhibited relatively regular morphology, with a few areas exhibiting uneven pore size due to thinning of the pore walls.

[0046] Example 4

[0047] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 0.5 wt.% NH₄F₂ and 0.25 wt.% H₂SO₄, respectively, and 0.3 wt.% Cr₂O₃. The anodization voltage was 25 V, and the anodization time was 40 minutes. Testing revealed that the surface nanotubes of the Ti-13Nb-13Zr alloy prepared exhibited a remarkably complete morphology, with uniform pore size, a regular and orderly array, and uniform wall thickness. There was no evidence of pore sealing or pore fusion.

[0048] Example 5

[0049] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 0.5 wt.% NH₄F₂, 0.25 wt.% H₂SO₄, and 0.3 wt.% Cr₂O₃. The anodic oxidation voltage was 30 V, and the anodic oxidation time was 60 minutes. Testing showed that the nanopores formed on the surface of the prepared Ti-13Nb-13Zr alloy had thick walls and were sealed.

[0050] Example 6

[0051] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 0.3 wt.% NH₄F₂, 0.25 wt.% H₂SO₄, and 0.3 wt.% Cr₂O₃. The anodic oxidation voltage was 30 V, and the anodic oxidation time was 40 min. Testing revealed that the nanotube morphology on the surface of the prepared Ti-13Nb-13Zr alloy exhibited more pronounced pore wall ablation compared to Example 3, with some pores exhibiting distortion and collapse, and adjacent nanopores merging to form larger pores.

[0052] Example 7

[0053] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 0.5 wt.% NH₄F₂, 0.25 wt.% H₂SO₄, and 0.3 wt.% Cr₂O₃. The anodization voltage was 20 V, and the anodization time was 40 min. Testing revealed that the surface nanotube morphology of the prepared Ti-13Nb-13Zr alloy was slightly less regular than that of Example 4, with some uneven pore size.

[0054] Example 8

[0055] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 0.5 wt.% NH₄F₂, 0.25 wt.% H₂SO₄, and 0.3 wt.% Cr₂O₃. The anodization voltage was 25 V, and the anodization time was 60 min. Testing revealed that the nanotube morphology on the surface of the prepared Ti-13Nb-13Zr alloy was slightly less regular than that of Example 4, with thinning of the pore walls in some areas and a small amount of fused nanopores.

[0056] Comparative Example 1

[0057] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 0.5 wt.% NH₄F₂ and 0.25 wt.% H₂SO₄, respectively, and 0.3 wt.% Cr₂O₃. The anodization voltage was 15 V, and the anodization time was 40 min. Testing revealed that the prepared Ti-13Nb-13Zr alloy surface nanotubes lacked a complete nanotube morphology, with nanotubes present in only a few areas. Furthermore, compared to Example 1, their arrangement was incomplete, with a greater number of sealed pores.

[0058] Comparative Example 2

[0059] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 0.3 wt.% NH₄F₂, 0.25 wt.% H₂SO₄, and 0.3 wt.% Cr₂O₃. The anodic oxidation voltage was 15 V, and the anodic oxidation time was 60 min. Testing revealed that the surface oxide layer of the prepared Ti-13Nb-13Zr alloy detached, but no nanotube morphology was formed.

[0060] Comparative Example 3

[0061] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 0.3 wt.% NH₄F₂, 0.25 wt.% H₂SO₄, and 0.3 wt.% Cr₂O₃. The anodic oxidation voltage was 40 V, and the anodic oxidation time was 10 minutes. Testing revealed no nanotube formation on the Ti-13Nb-13Zr alloy surface.

[0062] Comparative Example 4

[0063] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, with 1 wt.% NH₄F₂, 0.5 wt.% H₂SO₄, and 0.3 wt.% Cr₂O₃. The anodization voltage was 25 V, and the anodization time was 40 min. Testing revealed that the nanotubes formed on the surface of the prepared Ti-13Nb-13Zr alloy were irregular and often distorted, compared to those in Example 4.

[0064] Comparative Example 5

[0065] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, 1 wt.% NH₄F₂, and 0.5 wt.% H₂SO₄. The anodization voltage was 15 V, and the anodization time was 60 min. Testing revealed the nanotube morphology on the surface of the prepared Ti-13Nb-13Zr alloy. Compared to Example 1, pores formed on the surface under these conditions, but their shape could not be described as nanopores because the pores formed were disordered and did not form a nanotube array.

[0066] Comparative Example 6

[0067] The electrolyte composition consisted of ethylene glycol and deionized water in a 1:4 volume ratio, 1 wt.% NH₄F₂, and 0.5 wt.% H₂SO₄. The anodization voltage was 25 V, and the anodization time was 40 min. Testing revealed that the nanotube morphology on the surface of the prepared Ti-13Nb-13Zr alloy was not uniform in pore size and shape compared to Example 4.

Claims

1. A method for preparing titanium dioxide nanotube arrays on the surface of Ti-13Nb-13Zr alloy, characterized in that: The specific steps include: (1) Wire cutting: Wire cutting is performed on the Ti-13Nb-13Zr alloy rod to obtain the required sample and then clean it; (2) Sample polishing: Use sandpaper to polish the sample, and then use polishing cloth to polish it until the surface is scratch-free and presents a mirror finish; (3) Preparation of electrolyte: The electrolyte includes ethylene glycol, ammonium fluoride, sulfuric acid, chromium trioxide, and deionized water. The prepared electrolyte is placed in a constant temperature water bath and mechanical stirring is adjusted to ensure uniform mixing. The volume fraction ratio of ethylene glycol to deionized water in the electrolyte is 1:4, the mass fraction of ammonium fluoride is 0.5wt.%, the mass fraction of sulfuric acid is 0.25wt.%, and the mass fraction of chromium trioxide is 0.3wt.%; (4) Anodization: The sample treated in step (2) was placed in the electrolyte of step (3), and the Ti-13Nb-13Zr alloy sample was used as the anode and the graphite rod was used as the cathode. The anodization voltage and the anodization time were controlled to perform anodization to obtain a titanium dioxide nanotube array on the surface of the Ti-13Nb-13Zr alloy; the anodization voltage was 25 V and the anodization time was 40 min.

2. The method for preparing titanium dioxide nanotube arrays on the surface of Ti-13Nb-13Zr alloy according to claim 1, characterized in that: During the anodization process of step (4), mechanical stirring and a constant temperature water bath are continued to be maintained.

3. The method for preparing titanium dioxide nanotube arrays on the surface of Ti-13Nb-13Zr alloy according to claim 2, characterized in that: The constant temperature water bath temperature is 35° C., and the mechanical stirring speed is 160-180 r / min.

4. The method for preparing titanium dioxide nanotube arrays on the surface of Ti-13Nb-13Zr alloy according to claim 1, characterized in that: In step (3), the constant temperature water bath temperature is 35° C., and the mechanical stirring speed is 240 r / min.

5. The method for preparing titanium dioxide nanotube arrays on the surface of Ti-13Nb-13Zr alloy according to claim 1, characterized in that: The disc cut in step (1) has a thickness of 1 mm and a diameter of 10 mm and is ultrasonically cleaned using deionized water, acetone, and 95% alcohol in sequence.

6. The method for preparing titanium dioxide nanotube arrays on the surface of Ti-13Nb-13Zr alloy according to claim 1, characterized in that: In step (2), the sample is polished using sandpaper #240, #600, #1200, and #2000 in sequence. When the directions of the surface scratches are consistent, the polishing direction is changed orthogonally until the surface is smooth.

Citation Information

Patent Citations

  • Method of preparing TiO2 nano pipe array by anodic oxidation method

    CN101016637A

  • Titanium implant surface treatment method and implant manufactured by the same

    KR1020110082658A